2022
DOI: 10.1039/d2gc00698g
|View full text |Cite
|
Sign up to set email alerts
|

A case study in green chemistry: the reduction of hazardous solvents in an industrial R&D environment

Abstract: The 12 Principles of Green Chemistry act as a guide for chemists for the design and synthesis of sustainable product. Adoption by chemist is essential for the transition. We chose...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…This totality of assessment provides the basis for overall judgement about sustainability as well as for the concept and approach encapsulated in 'chemistry for sustainability '. 18 New reaction processes: Among the new and re-merging innovations currently receiving attention, those focusing on the sustainability of reaction processes, including the use of non-hazardous materials and conditions and applications of green solvents, 23 will be of particular interest to synthetic chemists. The search for more environmentally benign processes for chemical reactions has branched into a number of directions in recent years.…”
Section: Chemistry For Sustainable Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This totality of assessment provides the basis for overall judgement about sustainability as well as for the concept and approach encapsulated in 'chemistry for sustainability '. 18 New reaction processes: Among the new and re-merging innovations currently receiving attention, those focusing on the sustainability of reaction processes, including the use of non-hazardous materials and conditions and applications of green solvents, 23 will be of particular interest to synthetic chemists. The search for more environmentally benign processes for chemical reactions has branched into a number of directions in recent years.…”
Section: Chemistry For Sustainable Solutionsmentioning
confidence: 99%
“…Among the new and re-merging innovations currently receiving attention, those focusing on the sustainability of reaction processes, including the use of non-hazardous materials and conditions and applications of green solvents, 23 will be of particular interest to synthetic chemists. The search for more environmentally benign processes for chemical reactions has branched into a number of directions in recent years.…”
Section: Chemistry For Sustainable Solutionsmentioning
confidence: 99%
“…Indeed, there are several examples where ball-milled reactions proceed to completion in greatly reduced reaction times (likely as a consequence of their high effective concentration) and can lead to enhanced or altered selectivity and in some examples lead to products that are unobtainable by solution methods, as well as reduced sensitivity to air and moisture . From a sustainable process perspective, minimizing solvent use or removing undesirable solvents is a very attractive prospect . Nevertheless, solvents are an age-old technology taught at the undergraduate level; their use is familiar to all chemists.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the Sustainable Development Goals announced by the United Nations, Syngenta committed in 2020 to ambitious global sustainability objectives formulated through our Good Growth Plan Initiative . Our chemistry research department already reported initial progress toward reducing the usage of hazardous solvents . As an additional sustainability goal, we aim at reducing our overall consumption of precious metals whenever possible .…”
Section: Introductionmentioning
confidence: 99%